PENGARUH PRESEPSI CITRA PERUSAHAAN, KUALITAS LAYANAN DAN KEPUASAN TERHADAP KEPERCAYAAN NASABAH PT ANDALAN FINANCE DIVISI NASMOCO KREDITâ ( Studi pada PT. Andalan Finance Indonesia Cabang Semarang ) - Rachmah Sinta, 08.35.02.0730; Rizal R, Alimuddin (Students Journal of Economic and Management, 2012)
The purpose of this study was to examine the influence of corporate image and service quality as well as the satisfaction of the trust. Based on this study the researchers hoped to prove his hypothesis. The population in this study is the customer PT. Andalan Finance (division Nasmoco Credit ) in Semarang City. The determination of this sample using purposive sampling method with the criteria customers who have purchased a Toyota 1 times or more. The data in this research is obtained by distributing questionnaires to the respondents on 1 dealer Toyota in the Semarang City. For testing research hypothesis using multiple regression analysis. Based on the results of the study show that: (1) Corporate image has positive and significant impact on customer satisfaction. (2) The service quality has positive and significant impact on customer satisfaction. (3) Customer satisfaction has positive and significant effect on confidence. Thus all the hypothesis are either partially or jointly received significant levels are still below 5%. This study has one limitation of the study used data from a single source, where collection data on the limited research on the organization of the service company, and the sample size is only 110 where as the number of customers in the hundreds. Recommendations for research is limited to the influence of corporate image, service quality and customer satisfaction with confidence PT. Andalan Finance (division Nasmoco Credit). Key words: Corporate Image, Service Quality, Customer Satisfaction, and Customer Confidence